Penggunaan Media Pembelajaran Quiziz untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas V SDN Peterongan - Shanti Wahyuningsih Sasmito (Journal on Education, 2024)
The learning activities at SDN Peterongan still largely use classical methods, where the teacher explains and the students just listen. Initial observations showed that this method is not engaging for students, leading them to talk among themselves and lose focus during lessons. Quizizz as a learning medium has potential as an effective tool suitable for 21st-century students. The use of web-based educational media like Quizizz can make learning more engaging and improve the learning outcomes of fifth-grade students at SDN Peterongan Semarang. This classroom action research was conducted at SDN Peterongan Semarang during the first semester of the 2023/2024 academic year, targeting fifth-grade students, totaling 24 students, consisting of 11 boys and 13 girls. The data analyzed included both quantitative and qualitative data. Data collection methods included observation activities for teacher and student activities, as well as assessments or tests. The research findings showed that the percentage of students achieving mastery learning in cycle I was 75%, which increased to 88% in cycle II. From these data, it can be concluded that the use of Quizizz as a learning medium can significantly improve the mathematics learning outcomes of fifth-grade students at SDN Peterongan.Bagian Atas Formulir